The potency of bacteria isolated from the hydroponic rockwool of field mustard (Brassica rapa L.) for nitrogen fixation and indole acetic acid (IAA) production - Anindita Riesti Retno Arimurti; Vella Rohmayani; Nurhidayatullah Romadhon; Tara Puri Ducha Rahmani; Lee James Watson; Kenari Sri Wahyuni; Nova Ulumiya (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.